Orthodontic bone screws: A comprehensive review of applications and clinical outcomes and role of pharmacists - Alosaimi, Faisal Mohammed; Alshammari, Ibrahim Furih; Al Shamry, Mohammed Hamdan; Alamri, Abdulelah Mohammed Mubashir; Alsulaiman, Abdullah Ibrahim; Alharbi, Abdullah Jatil Mohammed; Almzairie , Khalid Ali; Almusallam, Mohannad Ali; Almutairi, Fayez Mohammed Hubayni; Al Nemer, Azzam Abdullah Rashed; Alshammari, Mohammed Tarish Sulbi; Albabtain, Mohammed Ibrahim Suliman (International journal of health sciences, 2021)
Background: Temporary Anchorage Devices (TADs), such as orthodontic bone screws, have revolutionized anchorage management in orthodontics. Since their introduction in 1997, TADs have been widely adopted to improve treatment outcomes, especially in complex malocclusions. Despite their efficacy, challenges such as high failure rates in inter-radicular (I-R) placement and limited clinical integration persist. Aim: This comprehensive review explores the clinical applications, outcomes, and barriers to adopting orthodontic bone screws, with a focus on extra-alveolar (E-A) TADs. Additionally, the role of pharmacists in optimizing patient care in orthodontic treatments involving TADs is examined. Methods: The review analyzes studies on TAD applications, clinical outcomes, and failure rates, emphasizing extra-alveolar sites such as the mandibular buccal shelf (MBS) and infra-zygomatic crest (IZC). It also discusses pharmacist contributions in medication management, patient education, and minimizing peri-implant inflammation. Results: E-A TADs demonstrated lower failure rates (7%) compared to I-R TADs (19.3%), with superior stability in IZC and MBS placements due to enhanced cortical bone contact. Pharmacists play a critical role in managing peri-implant inflammation, advising on hygiene practices, and providing medications that mitigate infection risks. Conclusion: TADs offer a reliable anchorage solution for complex malocclusions, with E-A placements yielding better outcomes.